2006
DOI: 10.1080/02770900600567122
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Asthma and Indoor Aeroallergens and Endotoxin in Palestine: A Case-Control Study

Abstract: This study was carried out to evaluate the relationship between wheezing or sensitization and concentrations of mites, cat and dog allergens, and bacterial endotoxin in Palestine. A nested case-control involved analysis of mattress and floor dust from a 110 children's houses with reported wheezing and without wheezing. We found no consistent associations between allergen levels and either wheeze or specific atopic sensitization. Furthermore, no clear associations between mattress endotoxin levels and wheeze or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
1
7
1
Order By: Relevance
“…Despite showing a protective effect of endotoxin on atopic asthma or wheeze, the study from Germany, Switzerland and Austria also found an increased risk of non-atopic wheeze with higher endotoxin levels among children from non-farming households [7] showing some disagreement with ours. A separate case–control study in Palestine that included 6 to 12 year old children [25] showed inverse associations between medium endotoxin levels from the mattress and being a non-sensitized case (report of wheeze in the past 12 months) compared to a non-sensitized control [25], in agreement with the results of our study. We found stronger protective effects of endotoxin among those without a history of allergic disease.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Despite showing a protective effect of endotoxin on atopic asthma or wheeze, the study from Germany, Switzerland and Austria also found an increased risk of non-atopic wheeze with higher endotoxin levels among children from non-farming households [7] showing some disagreement with ours. A separate case–control study in Palestine that included 6 to 12 year old children [25] showed inverse associations between medium endotoxin levels from the mattress and being a non-sensitized case (report of wheeze in the past 12 months) compared to a non-sensitized control [25], in agreement with the results of our study. We found stronger protective effects of endotoxin among those without a history of allergic disease.…”
Section: Discussionsupporting
confidence: 91%
“…We found stronger protective effects of endotoxin among those without a history of allergic disease. However, our observations regarding the personal history of allergy should be interpreted with some caution because of the lack of an objective measure of allergy and may account for the differences between our study and the study by Braun-Fahrländer et al [7,25] One explanation for our results could be the timing and duration of endotoxin exposure, both factors which could affect allergy and asthma onset. It may be that among those who did not have a history of allergy there was more early exposure to endotoxin prior to allergen exposure while those with a history of allergy had earlier exposure to allergens leading to sensitization.…”
Section: Discussioncontrasting
confidence: 74%
“…However, whereas some studies have shown a positive association between endotoxin and asthma (Ross et al 2000; Thorne et al 2005), others have suggested that LPS protects against development of this disease (Braun-Fahrländer et al 2002; El-Sharif et al 2006; Gehring et al 2004). In mice, very high doses of inhaled LPS have been previously reported to promote Th1 responses, with lower doses promoting Th2 responses (Eisenbarth et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Lipopolysaccharide (LPS), a major component of the outer cell wall of gram-negative bacteria, is ubiquitous in the environment, and some studies have indicated that exposure to relatively high levels of LPS during childhood protect against developing asthma later in life (Braun-Fahrländer et al 2002; El-Sharif et al 2006; Gehring et al 2004). Conversely, other studies have demonstrated a positive association between asthma and household levels of bacteria and LPS (Ross et al 2000; Thorne et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In our earlier study of children with asthma, we found that measured exposure (to levels above detection) and sensitization to Can f 1, but not to Fel d 1 were significantly associated with asthma morbidity (as measured by use of controller medication for ≥9 months during the year of follow-up) (Gent et al, 2009). Another study of asthmatic children where levels of pet allergen were measured found no associations between level of exposure and wheezing in analyses controlling for any atopic sensitization (El-Sharif et al, 2006). In contrast, two studies of adult asthmatics did find associations between risk of wheezing and specific sensitization/exposure status for measured levels of Fel d 1 (Gehring et al, 2001; Lewis et al, 2002).…”
Section: Discussionmentioning
confidence: 99%